Visitor center Äskhult; an architectural design investigation on the relationship between a specific context construction and space - Andersson, Amanda (My University, 2024)
Äskhults by, located in Halland County, is a several hundred year old village, which serves as one of the main tourist attractions in Halland today. Visitors get to experience how life was for the majority of the Swedish population over 200 years ago. Äskhults by’s unique buildings and village site were once surrounded by modern farmland and expanding spruce plantations. However, this landscape underwent a significant transformation in 1996. A large-scale project was initiated to restore the historical landscape around the farms, mirroring farming practices from 200 years ago, before the agrarian revolution. In the early nineteenth century, the village’s four farms encompassed arable land, hay meadows, enclosed pastures, and grazed outland. Today, these lands, along with the farmhouses, are protected as a cultural reserve, 132 hectares large. The post-and-plank construction is a several hundred year old technique mainly used in farmhouses, that was prominent in areas that had a shortage of trees. In Äskhults by the post-and-plank construction is clearly visible and makes up for most of the construction on site. The new visitor center should therefore be inspired by the construction and visual appearance of the historic site, however be thought of in a modern way. The research used a combination of methods, including “research for design”, “research by design”, literature studies, case studies, and site explorations. The aim of the thesis was to conduct an architectural design investigation on the relationship between a specific context, construction, and space, through the process of designing a visitor center for Äskhults by. With a special focus on developing the building technique post-and-plank construction, which is used in the majority of the farmhouses at Äskhult.
Keywords: Visitor center, building traditions, post-and-plank construction, Äskhults by